Eksplorasi Aktivitas Fundamental Matematika pada Aktivitas Etnomatematika dalam Merajut - Nur Hidayatin (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Ethnomathematics is a study that connects mathematical concepts with community culture, one of which is knitting activities. This study aims to explore the fundamental mathematical activities in knitting activities based on Alan Bishop's theory, namely counting, measuring, determining location, designing, playing, and explaining. This qualitative research uses an ethnographic approach. The data collection techniques are through observation, in-depth interviews, and documentation of knitters in the Jember Knitting Community (KRJ). Meanwhile, data analysis includes data reduction by filtering data that corresponds to the fundamental mathematical activities, data presentation, and drawing conclusions. The results of the study indicate that knitting activities contain six fundamental mathematical activities, namely measuring activities that appear in determining product sizes, designing activities that appear in compiling knitted product designs, determining location activities that appear in placing motifs on knitting, counting activities that appear in the process of counting stitches, playing activities that appear through exploration of motif and color variations, while explaining activities that appear in explaining knitting techniques and steps. In addition, knitting activities also contain various mathematical concepts, such as number patterns, arithmetic operations, measurement, geometry, symmetry, geometric transformations, creativity and mathematical reasoning, and mathematical logic. This research shows that knitting activities can be used as a resource for contextual, culture-based mathematics learning.